2013
DOI: 10.1007/s00203-013-0870-1
|View full text |Cite
|
Sign up to set email alerts
|

Could DNA uptake be a side effect of bacterial adhesion and twitching motility?

Abstract: DNA acquisition promotes the spread of resistance to antibiotics and virulence among bacteria. It is also linked to several natural phenomena including recombination, genome dynamics, adaptation and speciation. Horizontal DNA transfer between bacteria occurs via conjugation, transduction or competence for natural transformation by DNA uptake. Among these, competence is the only mechanism of transformation initiated and entirely controlled by the chromosome of the recipient bacteria. While the molecular mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 128 publications
(170 reference statements)
1
33
0
3
Order By: Relevance
“…Indeed, on the basis of a fitness disadvantage observed for a pilA − strain on chitin surfaces, it was previously suggested that the Tfp contributes to chitin colonization (15), although these fitness experiments were performed in a quorumsensing-defective strain of V. cholerae that is not naturally transformable. Interestingly, a secondary role for this Tfp would also support a recent hypothesis: Bakkali suggested that DNA uptake might be a side effect of Tfp-mediated bacterial adhesion and twitching motility (42); however, tDNA transfer through the periplasm and across the inner membrane would still require the presence of ComEA, ComEC, and ComF.…”
Section: Discussionsupporting
confidence: 59%
“…Indeed, on the basis of a fitness disadvantage observed for a pilA − strain on chitin surfaces, it was previously suggested that the Tfp contributes to chitin colonization (15), although these fitness experiments were performed in a quorumsensing-defective strain of V. cholerae that is not naturally transformable. Interestingly, a secondary role for this Tfp would also support a recent hypothesis: Bakkali suggested that DNA uptake might be a side effect of Tfp-mediated bacterial adhesion and twitching motility (42); however, tDNA transfer through the periplasm and across the inner membrane would still require the presence of ComEA, ComEC, and ComF.…”
Section: Discussionsupporting
confidence: 59%
“…To understand the contribution of the flagellar, the T3SS, and the T4P systems to the survival and movement of strain BS001, we included, next to the wild type, the respective mutant strains of these systems (denoted BS001 ΔfliF , BS001 ΔsctD , and BS001 ΔpilN [4, 5]) in all experiments. The inclusion of the mutants was justified based on previous indications that pH affects the expression and/or function of the T3SS [1517] and T4P/twitching motility [18, 19], whereas the flagellum is essential for strain BS001 migration in the mycosphere [4]. The cells were introduced at the “tip” or “middle” sites of the hyphal growth front in the soil compartment (denoted introduction site, see “Materials and methods” section).…”
Section: Resultsmentioning
confidence: 99%
“…Most transformation events are expected to be neutral or deleterious (the latter especially if using DNA from selectively killed cells [25]), and more immediate and reliable benefits of DNA uptake arise from DNA repair and nucleotide acquisition (57). A more extreme view is that DNA uptake could also be in part an unselected consequence of the adhesion and motility activities of T4P (58), though the coordinated regulation of the T4P genes responsible for DNA uptake and the non-T4P genes responsible for translocation into the cytoplasm argues against this. In this context, competence-induced cytoplasmic proteins coregulated with T4P genes take on special importance-are they modulations of the cellular response to their immediate environment or specific adaptations to promote transformation?…”
Section: The Mechanism and Function Of Natural Competencementioning
confidence: 99%